Partisipasi Masyarakat dalam Pelestarian Hutan Mangrove di Kelurahan Mangunharjo, Kecamatan Tugu, Kota Semarang - Fionita Yuliani Devi; Wakhidah Kurniawati (Jurusan Perencanaan Wilayah dan Kota, 2020)
Changes in the physical condition of mangrove forests that occur cannot be separated from human intervention, especially the local community. So that community involvement in efforts to conserve mangrove forests is needed. Therefore, the purpose of this research is to find out the participation model in the conservation of mangrove forests as a protected area in Mangunharjo Village, Tugu District, Semarang City. The method used in this study is qualitative, and uses interactive data analysis model techniques. The data used are primary data and secondary data. The results of the study showed that the form of community participation in the Mangunharjo Village was divided into two, namely (1) in the form of ideas, aspirations and inspiration as well as community expertise or skills in the mangrove farming community and the processed mangrove community, (2) in the form of energy as volunteers for the community outside the community in mangrove forest conservation activities. Community motivation to participate in the conservation of mangrove forests is divided into 3 namely psychological motivation, economic motivation, and motivation formed due to the presence of mangrove communities. Stakeholders involved in the conservation of mangrove forests in Mangunharjo Village are divided into several groups namely local communities, governments, non-profit institutions, non-profit organizations and outside communities, that each of these stakeholder groups has different roles from one another. they are interrelated, connected and influential so that they become a model of participation.